Postpartum Management of Hypertensive Disorders of Pregnancy in Six Large U.S. Hospital Systems: Descriptive Review and Identification of Clinical and Research Gaps - Palatnik, Anna; Hauspurg, Alisse; Hoppe, Kara K.; Yee, Lynn M.; Kulinski, Jacqueline; Khan, Sadiya S.; Sabol, Bethany; Yarrington, Christina D.; Freaney, Priya M.; Parker, Samantha E. (American Journal of Perinatology, 2024)
Hypertensive disorders of pregnancy (HDPs) are a key contributor to maternal morbidity and mortality. Several gaps in knowledge remain regarding best practices in the postpartum management of HDPs. In this review, we describe postpartum HDPs management among six large academic U.S. hospital systems: Medical College of Wisconsin, University of Pittsburgh, University of Wisconsin–Madison, Northwestern University, University of Minnesota, and Boston Medical Center. We identified that all six health systems discharge patients with HDPs diagnosed with a blood pressure (BP) cuff and use the same two antihypertensive medications, nifedipine and labetalol, as first- and second-line treatment of HDPs. Northwestern University routinely adds oral furosemide for 5 days for patients with BP that exceeds 150/100 mm Hg. Most hospital systems administer magnesium sulfate routinely when readmission for HDPs occurs. In contrast, there was variation in BP threshold for antihypertensive treatment initiation, use of remote BP monitoring program, use of a transition clinic, delivery or lack of education on long-term cardiovascular disease risk, and BP management through the first 6 weeks postpartum and beyond. Based on the clinical review, we identified clinical gaps and formulated considerations for research priorities in the field of postpartum HDPs management.
Keywords: hypertensive disorders of pregnancy; postpartum; remote monitoring; antihypertensive treatment